PERAN BUDAYA ORGANISASI MEMEDIASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PEMBERDAYAAN PSIKOLOGIS - Sthira Sista, Ni Made Mas Anindya; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2019)
Psychological empowerment is the employee's confidence in his ability in the process of capturing and understanding the state of the organization's environment as an act of motivation towards employees that relates to the skills and competencies they have. The purpose of this study was to determine the effect of transformational leadership on psychological empowerment, the influence of transformational leadership on organizational culture, the influence of organizational culture on psychological empowerment and the role of organizational culture to mediate the influence of transformational leadership on psychological empowerment. This research was conducted at the Office of Industry and Trade in Denpasar City. The number of samples taken was 50 contract employees who had worked for at least 1 year, with a saturated sample method. Data collection is done through interviews and observations. The data analysis technique used is path analysis. The results showed that transformational leadership has a positive and significant effect on psychological empowerment, transformational leadership has a positive and significant effect on organizational culture, a positive and significant organizational culture influences psychological empowerment and the role of organizational culture mediates transformational leadership on psychological empowerment. Keywords: psychological empowerment, transformational leadership, organizational culture